2012
DOI: 10.1007/s00266-012-9872-7
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Anchoring Sub-SMAS Face-lift

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors at http://www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This is achieved by sculpting the segmental sub-SMAS volume via tethering while simultaneously preserving the Bguardians of facial individuality,^i.e., the retaining ligaments and the zygomatic SMAS border (PRESTO). Most recently, Basile et al have reported an interesting technique that dissects the retaining ligaments and make a reduced tunneling release of the SMAS in order to facilitate upwards movement of the sub-SMAS volumetric tissue mass together with interconnecting structures [25]. However, this technique differs from the current one in that it does not employ the composite layer technique of Hamra [26], and therefore impacts less on the decisive midface and suborbital area.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by sculpting the segmental sub-SMAS volume via tethering while simultaneously preserving the Bguardians of facial individuality,^i.e., the retaining ligaments and the zygomatic SMAS border (PRESTO). Most recently, Basile et al have reported an interesting technique that dissects the retaining ligaments and make a reduced tunneling release of the SMAS in order to facilitate upwards movement of the sub-SMAS volumetric tissue mass together with interconnecting structures [25]. However, this technique differs from the current one in that it does not employ the composite layer technique of Hamra [26], and therefore impacts less on the decisive midface and suborbital area.…”
Section: Discussionmentioning
confidence: 99%
“…Two decades ago, it was reported that at least fifty percent of face-lift procedures included some sort of SMAS dissection [ 7 ], highlighting the importance of clarifying the morphology and spatial relationships of the fascial layers of the face and particularly the SMAS. Various SMAS techniques related to aesthetic surgery continue to be described in the literature [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%